Design, Analysis and Application of Dynamic Wireless Power Transfer Technique at High Switching Frequency for a Electric Vehicle Battery Chargers - Lalitha, B.; Divyapriya, S.; Amudha, A.; Emayavaramban, G.; Viyathukattuva; Ramkumar, M. Siva; Nivetha, M. (International Journal of Psychosocial Rehabilitation, 2019)
Wireless charging of Electric Vehicles (EVs) is made possible by Inductively Coupled Power Transfer (ICPT) system. This presents user convenience and safety issues are avoided. Battery charging applications, industrial loading machines, office appliances and medical sciences are the important applications of ICPT. For electric vehicle’s charging, ICPT system can be used successfully with some power transmission distance limitations. Overall circuit’s efficiency is reduced by this. In order to compute overall ICPT system’s optimum circuit parameter values, in Mat lab software, developed a mathematical model based simulation. Maximum efficiency is achieved by proposed design.